Studi Deskriptif Teknik Penerjemahan dan Kualitas Subtitle Bahasa Indonesia Film Purple Hearts - Lestari, Anggie Catur; Darmawan, I Nyoman Pasek (Ruang Kata, 2025)
This study aims to analyze the translation techniques and overall quality of the Indonesian subtitles in the film Purple Hearts, with the novel of the same title serving as a secondary source. The research employs a descriptive qualitative method using documentation as the data collection technique. Data were analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawaing with verification. Out of 125 identified subtitle segments, modulation was the most frequently applied technique (32%), followed by adaptation (17,6%), and literal translation (12%), while reduction was the least used (1,6%). The assessment of translation quality, based on Nababan dkk. (2015), shows that the subtitles are generally of good quality, with 72% accuracy, 76% acceptability, and 68% readability. Overall, the subtitles are considered accurate and natural, though some inconsistencies slightly affect the overall quality. The findings are expected to contribute to the development of audiovisual translation studies and serve as a practical reference for improving subtitle translation quality in Indonesia